Bound state solutions of Schrödinger equation for a more general exponential screened coulomb potential via Nikiforov-Uvarov method - Ita, Benedict Iserom; Ekuri, Phenomena; Isaac, Idongesit Okon; James, Abosede Olubunmi (Eclética Química, 2010)
The arbitrary angular momentum solutions of the Schrödinger equation for a diatomic molecule with the general exponential screened coulomb potential of the form V(r) = (− a / r)1+ (1+ br )e−2br has been presented. The energy eigenvalues and the corresponding eigenfunctions are calculated analytically by the use of Nikiforov-Uvarov (NU) method which is related to the solutions in terms of Jacobi polynomials. The bounded state eigenvalues are calculated numerically for the 1s state of N2 CO and NO.